Determining frying oil deterioration using chemical and physical methods - Frage Abookleesh, Frage Lhadi (2009)
This research was performed to assess the oil deterioration during deep fat frying. It was also conducted to compare and correlate oil quality parameters namely, total polar compound (TPC), free fatty acids (FFA), peroxide value (PV), P-Anisidine value (p-AV), specific extinction (E1%lcm233, 269nm), iodine value (IV), flavor, color, viscosity, with changes in the heating profile of melting point, and investigate changes in the properties of oils with different kinds of food during deep-fat frying of chicken, banana and sweet potato. The frying oil consisted of five types of commercial oils, namely, canola, corn, soybean, sunflower and palm olein. These oils were used to fry, banana, sweet potato and chicken at 185 ± 5°C for 6 hr per day for sixe days until the total time of 30 hours with an interval time of 20 min. One and half kilograms of each oil sample to be tasted and 100g of each fried product was used for the frying. The frying time was set for 7 minute for banana and sweet potato and 1 5 minute for chicken. Each day, fresh oil was added to replenish the oil used. Oils used were withdrawn on the following day and before starti ng the next frying cycle and was kept in the freezer at -20˚C. The oils were analyzed for PV, N, p-AV, FFA, E1%lcm233, 269nm, TPC, color, viscosity, flavor (by zNose) and thermal behavior (melting point by DSC). In this study, DSC was used to monitor the deterioration of frying oils during deep fat frying based on qualitative investigation of the thermal behavior (melting point). The investigation began with the successful comparison of the DSC thermal curves of five different vegetable oils. The heating thermogram for the oils showed varying degree of changes especially in the last melting peak position during the course of frying. The heating thermogram showed that there is one major peak and two small shoulders peaks and used the offset of last melting peak; ("the last order peak of the DSC heating thermogram was used to represent the changes in melting point"). Flavor analysis is typically performed by a qualitative analysis of zNose chromatogram. A novel approach using a surface acoustic wave (SAW) sensing based electronic nose for favor analysis was used in this study for detecting the losing of volatile compound in vegetables oils. A statistical correlation was carried out on the DSC heating thermogram with standard chemical and physical methods. Significant linear relationship was found between melting point, TPC, N, E1%1cm233 , 269nm and viscosity. The DSC heating thermogram showed excellent correlation (P<0.05) with the standard chemical analysis.The finding of this study reveals that palm olein showed significantly (P<0.05) lower in all measured parameters than the other oils used. The extent of oil deterioration was best reflected in the changes in percent TPC, N, E1%cm at 233nm